Does oral polio vaccine have non-specific effects on all-cause mortality? Natural experiments within a randomised controlled trial of early measles vaccine - Aaby, Peter (BMJ Open, 2016)
BACKGROUND: BCG and measles vaccine (MV) may have beneficial non-specific effects (NSEs). If an unplanned intervention with a vaccine (a natural experiment) modifies the estimated effect in a randomised controlled trial (RCT), this suggests NSEs. We used this approach to test NSEs of triple oral polio vaccine (OPV). METHODS: During an RCT of 2 doses of MV at 4.5 and 9 months versus 1 dose of MV at 9 months of age, we experienced 2 natural experiments with OPV. We assessed whether these OPV experiments modified the effect of 2-dose MV in the MV trial. SETTING: MV RCT conducted in urban Guinea-Bissau 2003–2009. INTERVENTIONS: Natural experiments with OPV due to missing vaccine and the implementation of OPV campaigns. MAIN OUTCOME MEASURE: Changes in the mortality rate ratio (MRR) for 2-dose MV versus 1-dose MV. RESULTS: First, the MRR (2-dose/1-dose MV) overall was 0.70 (0.52 to 0.94), but the MRR was 1.04 (0.53 to 2.04) when OPV at birth (OPV0) was not given, suggesting that early priming with OPV was important for the effect of 2-dose MV. The effect of OPV0 depended on age of administration; the MRR (2-dose/1-dose MV) was 0.45 (0.29 to 0.71) for children receiving OPV0 in the first week of life, but 3.63 (0.87 to 15.2) for those receiving OPV0 after the first month of life (p=0.007, test of no interaction). Second, campaign-OPV may have reduced the difference between the randomisation groups since the MRR (2-dose/1-dose MV) was 0.60 (0.42 to 0.85) for children who had not received campaign-OPV before RCT-enrolment versus 0.72 (0.23 to 2.31) and 1.42 (0.70 to 2.90) for children who had received 1 or 2 doses of campaign-OPV-before-enrolment, respectively. CONCLUSIONS: Bissau had no polio infection during this trial, so OPV0 and campaign-OPV may have NSEs since they modified the effect of 2-dose MV in an RCT. Different interventions may interact to a much larger effect than usually assumed.